CHARACTERISTICS OF TYPES OF DIABETES MELLITUS II IN REGIONAL GENERAL HOSPITAL THAN RONDAHAIM, SIMALUNGUN DISTRICT - Shofian Syarifuddin; Wilson Samosir (PT. Radja Intercontinental Publishing, 2022)
Complications caused by diabetes are becoming a more serious problem so controlling blood glucose intensively can reduce diabetes mortality by reducing complications that arise. This study aims to determine the characteristics of Type II Diabetes Mellitus Patients at Tuan Rondahaim Regional General Hospital, Simalungun Regency in 2019 With this type of research Descriptively, this research was carried out at the Tuan Rondahaim Regional General Hospital, Simalungun Regency from July to September 2019 with a total population of 40 people using the sampling technique, namely total sampling where all populations are sampled. The results of this study indicate that the younger a person has diabetes mellitus, it can be seen that the lower the number of people with diabetes mellitus,the number of people with diabetes mellitus is more suffered by women, there are fluctuations in the duration of the disease in the Toba and Simalungun tribes, while in the Javanese the longer they suffer from diabetes mellitus, there is a decrease in the incidence of duration of the disease with adherence to taking medication that has no significant difference compared to Duration of disease with adherence to diet There was a significant difference between adherents and non-adherents.where the tendency is not to comply with dict rules It is expected that Efarina University through the Bachelor of Nursing study program can provide counseling about Diabetes Mellitus, specifically Type II Diabetes Mellitus both in the community and in hospitals. adjusted to the portion and condition of the patient in this study, it can be included in the information that has been conveyed by researchers regarding type II Diabetes Mellitus sufferers.